On Social Dynamics Factors in Multi-stakeholder Decision Making in the Early State of Product Development - Ge,Ping; Hsieh,Ping-Hung (Journal of Design Research, 2007)
When design decisions are made by a group of diverse stakeholders, the decision making process is affected by both technical and social dynamic factors and the design results are consequently a product of the joint influences. Though it is important, the role of social dynamic factors in design process is currently not well understood. In this work, our study is focused on a prioritising problem concerning understanding customer needs at the early stage, in particular, identifying Quality Requirements and their relative importance. We introduced one among many social dynamic factors, i.e. trust and investigated its role in the early stage design decision making of product development. Derived from the definition and principle forms of general trust, the trust concept used in the prioritising problem for our study is specified. The existing measurement scales used in social science are modified for measuring the trust in terms of trustworthiness.
Keywords: Supply Chain

Using an Updating Urn-scheme for Prioritzing Quality Requirements in the Early Stage of Collaboration Design - Hsieh,Ping-Hung; Ge,Ping; Meier,Stefan (Journal of Design Research, 2007)
Keywords: Supply Chain